Mechanical asymmetries remain low-to-moderate during 30 min of self-paced treadmill running - Khouloud Mtibaa (10110879) (2023)
Introduction We characterized the magnitude and range of gait asymmetry during self-paced treadmill running. Methods On an instrumented treadmill, twelve trained runners (11 males, 1 female) completed a 30-min self-paced run, during which participants were instructed to cover the most distance possible. Ground reaction force recordings at a constant velocity corresponding to 70% of their maximal aerobic velocity (13.3 ± 0.8 km.h−1) allowed for the measurement of running kinetics and kinematics, as well as the calculation of spring-mass characteristics at the beginning, middle, and end of the run (minutes 1, 14, and 29, respectively). Group mean asymmetry scores were assessed using the “symmetry angle” (SA) formulae, where scores of 0% and 100% represent perfect symmetry and perfect asymmetry, respectively. Results There was no time effect on SA scores for any of the 13 biomechanical variables (p ≥ 0.128). Mean SA scores were <2.5% for contact time (0.8% ± 0.7%), flight time (1.4% ± 0.6%), step frequency (0.7% ± 0.3%), duty factor (0.7% ± 0.3%), duration of braking (1.3% ± 0.7%) and push-off phases (0.9% ± 0.8%), as well as peak braking (2.3% ± 1.3%) and push-off forces (1.4% ± 0.9%). Mean SA scores were ≥2.5% for peak vertical loading rate (3.1% ± 1.7%), mean vertical loading rate (3.4% ± 2.1%), peak vertical forces (2.9% ± 2.2%), as well as vertical stiffness (5.2% ± 3.5%) and leg stiffness (2.5% ± 1.5%). Conclusion Throughout a 30-min running time trial, there were consistently low-to-moderate mechanical asymmetries for spatiotemporal variables, kinetics, and spring-mass model characteristics. This suggests that trained runners maintained relatively even strides during the self-paced treadmill run, with lower extremities behaving similarly when controlling for velocity. Other Information Published in: Frontiers in Physiology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fphys.2023.1289172